Emerging Architectures in Direct-Clip Optical Communication: A Comprehensive Review - Aymen Abdalmunam Hameed (المجلة الدولية للحاسبات والمعلوماتية, 2026)
The global demand for ultra-high-speed data transmission intensifies, Intensity-Modulation Direct-Detection (IM/DD) systems have recently turned as the pillar of short-reach optical networks like 5G/6G front haul, hyper-scale data-centres and Optical Wireless Communication (OWC/Li-Fi). Out of all the modulation candidates, Direct-Current Biased Optical Orthogonal Frequency Division Multiplexing (DCO-OFDM) is one of the most promising modulation formats due to the benefits of high spectral efficiency and immunity to the multipath fading and ISI due to the inherent nature of this format. Nonetheless, high DC bias currents must be used to prevent signal clipping in optical emitters (e.g., Light Emitting Diodes (LEDs) and Laser Diodes (LDs)) due to the large power fluctuations, which results in inefficient energy utilization and an accelerated deterioration of the component. In addition, if these peaks become larger than the small linear dynamic range of inexpensive hardware then they cause strong non-linear distortion, greatly increasing the Bit Error Rate (BER) while also limiting the modulation order possible (e.g. 64-QAM to 1024-QAM). This review totally examines the Direct Clip framework a further developed type of digital flag handling (DSP) that is utilized to limit these impediments. While typical clipping regards signal peaks as random errors, Direct Clip takes advantage of Iterative Clipping and Filtering (ICF) and Noise Shaping to actively push the signal envelope into the ideal domain of operation for hardware. This paper illustrates the trade-offs between computational complexity, spectral leakage, and fidelity through individual blocks to show how Direct-Clip architectures facilitate the utilization of low-resolution Digital-to-Analog Converters (DACs) and non-linear optical components for high-throughput applications. These findings confirm that Direct-Clip Optical-OFDM is much more than an incremental advance, but rather one of the core building blocks for sustainable, low-cost, high-capacity Optical connectivity at the next level of software-defined networks.